2014
DOI: 10.2174/0929867320666131119121108
|View full text |Cite
|
Sign up to set email alerts
|

Biological Implications of Selenium and its Role in Trypanosomiasis Treatment

Abstract: Selenium (Se) is an essential trace element for several organisms and is present in proteins as selenocysteine (Sec or U), an amino acid that is chemically distinct from serine and cysteine by a single atom (Se instead of O or S, respectively). Sec is incorporated into selenoproteins at an in-frame UGA codon specified by an mRNA stem-loop structure called the selenocysteine incorporating sequence (SECIS) presented in selenoprotein mRNA and specific selenocysteine synthesis and incorporation machinery. Selenopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…During the last years, various reports have shown recognition of an increase in plasma selenium levels as a new defensive strategy against Leishmania infection (14,15). The choice of the chemical form for the selenium derivatives can modulate the level of this element on the basis of several metabolic routes (16).…”
mentioning
confidence: 99%
“…During the last years, various reports have shown recognition of an increase in plasma selenium levels as a new defensive strategy against Leishmania infection (14,15). The choice of the chemical form for the selenium derivatives can modulate the level of this element on the basis of several metabolic routes (16).…”
mentioning
confidence: 99%
“…In addition, there is growing evidence suggesting a connection between selenium (Se) and parasites, particularly trypanosomatids. In fact, some parasites express selenoproteins (3,4) and metabolize Se (5).…”
mentioning
confidence: 99%
“…Se derivatives have been shown to reduce parasitemia (3,6). Furthermore, they also decrease clinical manifestations (7,8) and mortality in infected mice.…”
mentioning
confidence: 99%
“…Studies have shown that Trypanosoma and Leishmania are sensitive to auranofin, a potent selenoprotein inhibitor; however, the probable drug mechanism is not related to selenoproteins in kinetoplastids. Latest studies have also shown that Selenium supplementation decreases the parasitemia of various Trypanosome infections and reduces important parameters associated with diseases such as anemia and parasite-induced organ damage (Da Silva et al, 2014). It is, thus, interesting to understand the sequence level information of the proteins involved in Seleno-cysteine biosynthesis in Leishmania donovani .…”
Section: Resultsmentioning
confidence: 99%